2017
DOI: 10.1101/238303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mathematical models for cell migration with real-time cell cycle dynamics

Abstract: (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint . http://dx.doi.org/10.1101/238303 doi: bioRxiv preprint first posted online Dec. 21, 2017; extended models, which can take the form of travelling waves. These solutions are mathematically interesting because they are a combination of moving wavefronts and moving pulses. We derive and confirm a simple analytical expression for the minimum wave spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 41 publications
(70 reference statements)
1
32
0
Order By: Relevance
“…As stated previously, formal travelling wave solutions are almost never observed experimentally. Typical scratch assays initial configurations lead to two opposingly-directed fronts, such as the profiles in Figure 2(d), (h), (l) and pshowing the evolution of the Generalised Porous Fisher model for several values of r. Note that, for typical scratch widths, wound closure takes place before travelling waves have an opportunity to form (Jin et al, 2016b;Vittadello et al, 2018). However, the value of r still impacts the wound closure rate and the shape of the moving font.…”
Section: Modelling Cell Populations With Reaction-diffusion Equationsmentioning
confidence: 97%
See 1 more Smart Citation
“…As stated previously, formal travelling wave solutions are almost never observed experimentally. Typical scratch assays initial configurations lead to two opposingly-directed fronts, such as the profiles in Figure 2(d), (h), (l) and pshowing the evolution of the Generalised Porous Fisher model for several values of r. Note that, for typical scratch widths, wound closure takes place before travelling waves have an opportunity to form (Jin et al, 2016b;Vittadello et al, 2018). However, the value of r still impacts the wound closure rate and the shape of the moving font.…”
Section: Modelling Cell Populations With Reaction-diffusion Equationsmentioning
confidence: 97%
“…These solutions are of general mathematical interest and have been extensively studied (Harris, 2004;Witelski, 1995). However, since travelling waves only occur as in the long-time limit and require rather special initial conditions, travelling waves are rarely observed experimentally (Jin et al, 2016b;Vittadello et al, 2018). Therefore, we do not consider connecting any kind of travelling wave solutions with experimental data in this work.…”
Section: Modelling Cell Populations With Reaction-diffusion Equationsmentioning
confidence: 99%
“…Previous work has shown that heterogeneity in cell age distribution may still generate logistic growth at the population scale [22]. Other age-structured models have described how the cell age distribution can affect the overall cell population dynamics in scratch assays: the speed with which the cells invade the vacant region [19,44], the efficacy of anti-cancer drugs, particularly phase-specific drugs [5] and the influence of growth factors [6]. Agent-based models have also been considered to study the effect of heterogeneity in cell age distribution on the overall dynamics in in-vitro assays [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…trajectory data is an active area of research (Hywood et al, 2021), but we find using the Simpson et al (2018) model which incorporates cell trajectory data leads to a good outcome.…”
mentioning
confidence: 81%
“…The copyright holder for this preprint this version posted April 21, 2021. ; https://doi.org/10.1101/2021.04.20.440712 doi: bioRxiv preprint 2 Data 2D scratch assay experiments are a good screening tool for more complex experimental models, as they are low cost, allow for easy data interpretation and readily allow control of oxygen, nutrients and drug supply (Beaumont et al, 2014;Santiago-Walker et al, 2009). We adopt data from a study conducted by Vittadello et al (2018) where a scratch assay is used to examine melanoma cell proliferation and migration in real time with FUCCI technology. The experiment is initialised by placing a small population of cells and a growth medium in a culture dish (Figure 1 (a)) to create a uniform 2D monolayer of cells.…”
mentioning
confidence: 99%